Primary energy efficiency potentials of district heat driven refrigeration systems. (October 2021) - Hausherr, Carsten; Petersen, Stefan; Hüls, Walther; Albers, Jan
Abstract: District heat driven absorption chillers (AChs) contribute to a higher utilisation of the district heating network in summer and thus to a reduction of the relative heat losses. Due to higher investment but lower operating costs, AChs usually cover the base load, but compression chillers (CChs) are installed for peak load as well. For ACh and CCh, heat rejection is often realised via cooling towers (CTs). In addition, many systems provide the option of free cooling in winter by using the cooling towers to cover the cooling demand directly. Thus, absorption cooling (AC), compression cooling (CC) and free cooling (FC) represent three operating modes for cold generation in one overall refrigeration system. The concept of allocating base load and peak load is usually realised by activating CC when AC exceeds the capacity limit. FC is activated when the ambient temperature falls below a certain switchover value. In this study, extensive monitoring data from a large-scale field test ("Field test absorption chillers for CCHP systems") are used to show that refrigeration systems controlled in such or similar ways have considerable potential to increase primary energy efficiency, even if the individual chillers are operated efficiently. Therefore, models are applied to the individual primary components (ACh, CCh, CT and auxiliary pumps). By using these models, thermal and/or electrical part-load efficiencies of AC, CC and FC and their specific dependencies on the ambient temperature and chilled water set temperature are calculated. Taking into account district heating and electricity primary energy factors allows to determine the operating mode with the lowest primary energy demand for each load condition measured in the field test within one year. The savings potential of 14% resulting from this example shows how promising the application of a model-based system control is compared to conventional strategies.